Additional file 2 of Psychometric validation and measurement invariance of the self-compassion scale-short form (SCS-SF) across gender, clinical population, and cultures - Büyüköksüz, Engin; Tekin, Işıl; Arıkan, Serkan; İlkay, Şengül; Erözkan, Atılgan (figshare, 2025)
Supplementary Material 2